Peningkatkan Keterampilan Menulis Permulaan melalui Buku Harian Bergambar Siswa Kelas II B SD Timbulharjo Sewon Bantul - Wahni Hidayah (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2019)
This research aims at improving the 2nd grade students’s early writing skills using Illustrated Diary in SD Timbulharjo. The subjects were all students of 2nd class (25 students). The object of this research was the enhancing of 2nd B class students's early writing skills. This research use the Kemmis and Mc. Taggart’s design. The data collection’s methods using observation, test (performance), and documentation. Data were analyzed using qualitative and quantitative descriptive. The results shows that the IInd B class student’s early writing skills have enhanced during the action. The results obtains from the comparison of the class’s completeness percentage on Pra Cyle, Ist Cycle, and 2nd Cycle. Student’s completeness percentage on Pra Cycle was 36% (9 students) with “less” criteria have increased to 52% (13 students) on Cycle Ist with “enough” criteria. On Cycle IInd, student’s completeness percentage have increased to 76% (19 students) with “good” criteria.